Competition between Gyranusoidea tebygi and Anagyrus mangicola, parasitoids of the mango mealybug, Rastrococcus invadens: interspecific host discrimination and larval competition - Bokonon-Ganta, A.H.; Alphen, J.J.M. van; Neuenschwander, Peter (Wiley, 1996)
The competition between Gyranusoidea tebygi Noyes and Anagyrus mangicola Noyes (both Hymenoptera: Encyrtidae), exotic parasitoids of the mango mealybug, Rastrococcus invadens Williams (Homoptera: Pseudococcidae) was studied in the laboratory. No significant differences were found in the way each parasitoid species examined, attacked, stung, and oviposited into hosts, unparasitized, or previously parasitized by the other species. This suggests that neither species discriminates against each other. The total number of parasitoids of either species emerging did not significantly differ between competition experiments. When A. mangicola was the first parasitoid to attack a host, it had no significant advantage over G. tebygi. However, when A. mangicola followed G. tebygi by either 4 or 24 h, it clearly won. Overall A. mangicola won the competition in 70.9% of all cases. The level of the competition, either at the egg or larval stage, and factors responsible for the elimination of older larvae by younger ones could not be assessed in these experiments. The coexistence of the two parasitoids as complementary for the biological control of the mango mealybug is discussed.